Bonnie's new toy - Liu, Cynthea (Step into reading., 2026)
"The toys are back in Disney and Pixar's Toy Story 5, and this time, it's Toy meets Tech. Buzz, Woody, Jessie, and the rest of the gang's jobs are challenged when they're introduced to what kids are obsessed with today . . . electronics! Directed by Andrew Stanton, co-directed by McKenna Harris, and produced by Jessica Choi, Toy Story 5 opens only in theaters on June 19, 2026. Kids will love this Step 2 leveled reader based on the film! -- Step 2 readers use basic vocabulary and short sentences to tell simple stories. They are for children who recognize familiar words and can sound out new words with help." --